2000
DOI: 10.1097/00007890-200003150-00065
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Susceptibility to Renal Ischemia Reperfusion Injury Revealed in a Murine Model

Abstract: NIH Swiss mice appear to be resistant in susceptibility to renal IRI. Early expression of pro-inflammatory genes was not associated with resistance to IRI, thus genetic factors could be important in outcome after renal IRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 9 publications
1
35
2
Order By: Relevance
“…But, da Silva et al (2007) and Kale et al (2003) reported no mice survived more than 24 hr when submitted to 35-45 min of bilateral renal ischemia with male C57BL/6 mice and Rosa26 mice, respectively. The discrepancy with our results is probably due to mouse strain differences (Burne et al 2000).…”
Section: Discussioncontrasting
confidence: 99%
“…But, da Silva et al (2007) and Kale et al (2003) reported no mice survived more than 24 hr when submitted to 35-45 min of bilateral renal ischemia with male C57BL/6 mice and Rosa26 mice, respectively. The discrepancy with our results is probably due to mouse strain differences (Burne et al 2000).…”
Section: Discussioncontrasting
confidence: 99%
“…There are several possible mechanisms that may help explain the difference in results compared with previous reports (33,34). Different genetic backgrounds may contribute to this difference in observed injury (53). This might result from pleiotropic functions of OPN as aforementioned.…”
Section: Discussionmentioning
confidence: 76%
“…In contrast, OPN-null mice have reported to have more pronounced IRI (higher creatinine level and kidney histological abnormality) than wildtype mice, which would support a renoprotective function of OPN on TECs (34). The reason(s) for this discrepancy is unknown but may be due to the variable resistance and susceptibility of different mouse strains to IRI (53). In our model, OPN-null mice clearly had less severe kidney injury with reduced creatinine levels, less tissue damage, and fewer infiltrating NK cells.…”
Section: Discussionmentioning
confidence: 98%
“…Variables previously shown to affect performance in response to hepatic IRI are animal sex (Harada et al 2004) strain (Burne et al 2000, Shireman & Quinones 2005, Dodd et al 2006) and intraoperative temperature regulation (Biberthaler et al 2001, Kato et al 2002, Khandoga et al 2003. These factors have been tested in heterogeous models of hepatic IRI, and as a result, experiments cannot be directly compared; their results are difficult to apply directly to the development of new experimental models.…”
Section: Discussionmentioning
confidence: 99%